Variation in wing length in relation to sex and age of Marsh Tits Parus palustris - Nilsson, Jan-Åke (Ornis Svecica, 1992)
Wing length of juvenile and adult Marsh Tits Parus palustris was measured during autumn and winter. Individuals later sexed during breeding were used to study a possible sexual dimorphism in wing length. Males of both juveniles and adults had significantly longer wings than females, the difference between the sexes being around 5.5%. Using wing length as the only criterion, between 97.4% and 88.6% of juveniles and between 98.0% and 93.4% of adults can be unambiguously sexed during autumn/winter. Individuals measured during their second or later autumn/winter had significantly longer wings than those measured as juveniles. No evidence for selection against short-winged individuals was found. Each individual increased its wing length during the first complete moult. Hypotheses explaining an increase in wing length with age are discussed and I argue that the best explanation encompasses some sort of nutritional constraint during the nestling and/or early fledgling phase.